Doctoral student mentorship in social work education: a Canadian example. (16th November 2018) - Fulton, Amy Elizabeth; Walsh, Christine A.; Gulbrandsen, Carolyn; Tong, Hongmei; Azulai, Anna
Abstract : Purpose: This paper aims to present a thematic analysis investigating the experiences and reflections of doctoral students in social work at a Canadian university who were mentored in the development of teaching expertise, including course design, delivery and evaluation, by a senior faculty member. Recommendations to others who are considering engaging in doctoral student teaching mentorship are presented. Design/methodology/approach: The paper examines the authors' reflections on their experiences of doctoral student mentorship through their involvement in collaboratively designing, teaching and evaluating an online undergraduate course. The inquiry used a qualitative approach grounded in Schon's concept of reflexive learning. Findings: Based on the results of the thematic analysis of the mentees' reflections, this paper presents the collaborative teaching mentorship model and discusses how receiving mentorship in teaching facilitated the mentees' development as social work educators. Originality/value: Although quality guidelines in social work education recommend that doctoral students should be adequately prepared for future teaching opportunities, there is limited discussion about doctoral student development as educators within the academic literature, especially from the perspective of doctoral students. There is also limited articulation of specific models of doctoral student mentorship in developing teaching expertise. The authors hope that sharing their reflections on their experiences and describing the collaborative teaching mentorship model will serve to deepen understandings and promote further exploration and development of doctoral student mentorship in teaching.